Penyuluhan Kesehatan Upaya Pencegahan Penyakit Tidak Menular Dan Pendampingan Demonstrasi Makanan Berbahan Pangan Tradisional - Sembiring, Endam Apulina Br; Setyawati, Retno; Rasyid, Djusmadi; Putri, Safridha Kemala; Nursinah, A.; Juwariyah, Siti; Rizki, Zuriani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Non-communicable diseases are closely related to changes in human lifestyles that lack physical activity and poor eating habits. Therefore, non-communicable diseases can be prevented by changing to a healthy lifestyle. One way to overcome non-communicable diseases in the elderly is to conduct regular health checks and consume healthy foods. This community service activity aims to conduct health checks on 27 elderly people in Komba Village in the form of health checks. Elderly people who experience health problems are given nutritional counseling, then a demonstration of making Kapurung snacks using local food ingredients is carried out. The results of the activity have a positive impact on the elderly where 100% of the elderly have undergone health checks in the form of blood pressure, blood sugar and cholesterol checks, increasing knowledge in the elderly is carried out through nutritional counseling and actively participating in demonstration activities for snacks using local ingredients.